ISLAMIC BANKING AND SOCIAL RESPONSIBILITY: STUDI KOMPARASI INDONESIA DAN MALAYSIA DENGAN PENDEKATAN ISLAMIC SOCIAL RESPORTING INDEKS DAN GLOBAL REPORTING INITIATIVE INDEKS - Nispa Sari (EKSPOSE, 2017)
This study aimed to compare the social performance between Islamic banking in Indonesia and Malaysia were measured by using a model of Islamic Social Reporting Index (ISR) and the Global Reporting Initiative Index (GRI). The objects of this study were drawn from four Islamic banks in Indonesia and three Islamic banks in Malaysia that meet certain criteria, namely; Islamic banking report annual report for 2010 and report the social responsibility disclosure. This study was used content analysis approach. The results showed that the overall average social performance of Islamic banking in Malaysia higher than social performance of Islamic banking in Indonesia. However, when tested statistically, the difference did not show significant value. Moreover, there are no Islamic banking in Indonesia and Malaysia reached a perfect level of social performance (100%) of the ISR and the GRI index.